Peran Infaq dan Shadaqah dalam Mewujudkan Keadilan Sosial: Kajian Tematik Al-Qur’an dan Hadis - Nida Nurhayani Pohan; Nurhayati; Yenni Samri Juliati Nasution (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2025)
This study aims to analyze the concepts of infaq and sadaqah in the Qur'an and Hadith through a qualitative approach using the maudhu'i (thematic) method. The theological-normative approach is used to explore the meaning of Islamic teachings on generosity, while the social approach is utilized to examine their relevance in contemporary Islamic philanthropic practices. Data were collected through a literature review of Qur'anic verses, Hadith, tafsir books, Islamic jurisprudence literature, Islamic economics, and previous research. The study results indicate that infaq and sadaqah play a strategic role in realizing social justice through the distribution of assets that is trustworthy, equitable, and oriented toward empowerment. The research findings also reveal the need to integrate Islamic normative principles with the design of a modern ZIS program that is more participatory, measurable, and sustainable. This study offers a conceptual model that can serve as a basis for maintaining Islamic philanthropic management to make it more effective, contextual, and have a real impact on society.